How Do Nurses Apply Personal Knowing to Patient Care? A Grounded Theory Study - Forough Rafii; Fereshteh Javaheri Tehrani; Alireza Nikbakht Nasrabadi; Shabnam Shariatpanahi (Iran University of Medical Sciences, 2021)
Background: Personal Knowing (PK) is an expression of self-knowledge concerning others. Besides, PK is the most difficult as well as the most essential pattern of knowing in nursing. The current study aimed to explore how nurses apply personal knowledge in patient care. Methods: This qualitative study was performed based on the grounded theory method. The study was performed in different hospital wards of Tehran City, Iran. The required data were generated using semi-structured interviews and clinical observations. Finally, 15 interviews and 8 sessions of observation were included in the data analysis. Strauss and Corbin's constant comparison method (2008) was used to analyze the collected data. Results: The obtained findings suggested that nurses use the PK pattern in 3 forms of the therapeutic use of self, self-centering, and elimination of therapeutic communication. The therapeutic use of self was accompanied by kindness and amiability; efforts to strengthen the patients' spirit; giving comfort and hope; humor; talking in a friendly manner, and gaining the patient's trust and cooperation. Self-centering was characterized by establishing silence in the ward, strict enforcement of the rules, setting more rules, and developing rules for the method of care provision. Eliminating the therapeutic communication was accompanied by the referral of patients to others, avoidance, reluctance, and mechanical care. Conclusion: The obtained findings added to the knowledge of the patterns of knowing in nursing. The therapeutic use of self leads to a positive outcome of care as well as the satisfaction of nurses and patients. However, a self-centering and eliminating therapeutic relationship will raise an inappropriate image of nursing.